La reforma de Córdoba: calidoscopio de ideas y laboratorio de experiencias en America Latina y El Caribe - Tcach, César (SocietàMutamentoPolitica, 2018)
Throughout the twentieth century, reformism - which had its origin in the Cordoba movement in 1918 - was part of an extended political culture in Latin America that was nourished and resignified to the rhythm of elements present in the own configurations of values and representations existing in the different countries: anticlericalism and anti-imperialism-fundamentally in an anti-American key-in Mexico and Cuba; radicalism and socialism in Argentina, Batllismo and ethical anti-imperialism in Uruguay, Indo-Americanism and Marxism in Peru; the anti-conservative rebellions in Colombia, and the anti-dictatorial and anti-authoritarian combat in most of the countries of the continent. Three matrices operated against the reformist waves: the state-authoritarian, the clerical and the dictatorial military itself.